2003
DOI: 10.1103/physrevb.67.064406
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional magnetic transition and transport behavior inNa0.75CoO2

Abstract: Here we report an unconventional magnetic and transport phenomenon in a layered cobalt oxide, NaxCoO2. Only for x = 0.75, a magnetic transition of the second order was clearly detected at Tm ∼ 22 K where an apparent specific-heat jump, an onset of extremely small spontaneous magnetization, and a kink in resistivity came in. Moreover large positive magnetoresistance effect was observed below Tm. These features of the transition strongly indicate the appearance of an unusual electronic state that may be attribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
193
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(217 citation statements)
references
References 19 publications
23
193
1
Order By: Relevance
“…Although the origin of the large thermopower remains a subject of active investigation, strong correlations between Co d electrons and spin entropy are believed to play a critical role 3,4,5 . Beside its unusual thermoelectric properties, Na x CoO 2 (x in the range 0.5 ∼ 0.75) is also known for having a Curie-Weiss type of susceptibility instead of a Pauli paramagnetic behavior 6,7,8 , which would be more compatible with its metallic conduction 6 . Although there have been reports of a weak magnetic ordering transition in Na 0.75 CoO 2 at T m = 22 K 8,9 , no such transition has been observed down to 2 K for systems with lower Na contents.…”
Section: Introductionmentioning
confidence: 99%
“…Although the origin of the large thermopower remains a subject of active investigation, strong correlations between Co d electrons and spin entropy are believed to play a critical role 3,4,5 . Beside its unusual thermoelectric properties, Na x CoO 2 (x in the range 0.5 ∼ 0.75) is also known for having a Curie-Weiss type of susceptibility instead of a Pauli paramagnetic behavior 6,7,8 , which would be more compatible with its metallic conduction 6 . Although there have been reports of a weak magnetic ordering transition in Na 0.75 CoO 2 at T m = 22 K 8,9 , no such transition has been observed down to 2 K for systems with lower Na contents.…”
Section: Introductionmentioning
confidence: 99%
“…For x in the 0.5 -0.75 range, the susceptibility χ(T ) is Curie-Weiss-like (C-W) with reported moment of the order of magnitude 1 µ B per Co 4+ [2,3] which indicates the presence of correlated electron behavior on the Co ions. Magnetic ordering at 22 K with very small ordered moment has been reported for x=0.75 [9] and Wang et al measured field dependence [4] that indicated the spin entropy of the magnetic Co system is responsible for the unusual thermoelectric behavior. Thus for x ≥ 0.5 magnetic Co ions and magnetic ordering give evidence of correlated electron behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the large thermopower, these Co oxides show many interesting properties. For example, Na x CoO 2 exhibits magnetic order(x ∼ 0.75), charge order(x ∼ 0.5), and even superconductivity(x ∼ 0.35) in its hydrated form [8,9,10]. Bi-SrCo-O compound shows pseudogap, ferromagnetism, and negative magnetoresistance [5,11].…”
Section: Introductionmentioning
confidence: 99%